LEGAL PERSFECTIVE OF CYBERBULLYING AND MENTAL HEALTH OF TEENEGERS IN INDONESIA - Meria Utama; Irsan Irsan; Achmad Romsan; M Rasyid; Muhammad Zainal Fikri (Fakultas Kedokteran Universitas Sriwijaya, 2022)
progress not only has a positive impact on human life but, at the same time, becomes a practical media for someone to commit an unlawful act. Crimes that are rife in cyberspace are body shaming and cyberbullying, so it is not impossible that with the development of the era with information technology and various kinds of social networks, these actions will become more widespread and can have a negative impact on survival, especially in the mental health of adolescents. Therefore, it is interesting to discuss the problem of how the correlation between legal aspects and cyberbullying and its impact on children's mental health. The method used in this study is by tracing through library research. The results showed that cyberbullying occurs a lot in Indonesia, among adolescents aged 13 to 17 years. The various impacts of this bullying are emotional impacts, mental impacts, social impacts, and legal impacts. That the government has taken various actions both preventively and repressively, so that both perpetrators and victims can be handled properly. For this reason, the cooperation of many parties is needed so that cyberbullying does not endanger both from a legal and health perspective. The results showed that cyberbullying occurs a lot in Indonesia among adolescents aged 13 to 17. The impacts of this bullying are emotional, health mental, social, and legal impacts. The government has taken various actions preventively and repressively so that the actors and victims can be handled properly. Therefore, cooperation of many parties is needed to decrease this kind of action, and relating to mental health, the victims is better to see the psychologist, or someone trusted to get some advises. Increasing the confidence and release the anxiety for the teenagers’.